Stability analysis for coupled multilayer graphene nanoribbon interconnects. (December 2016) - Qian, Libo; Xia, Yinshui; Ge, Shi; Ye, Yidie; Wang, Jian
Abstract: Based on equivalent single conductor (ESC) concept for multilayer graphene nano-ribbons (MLGNRs), this paper establishes the distributed transmission line model of coupled MLGNR interconnects and derives the analytical expression of coupled transfer function. Using the proposed model and Nyquist stability criterion at the global level of 14 nm technology node, the impact of switching factor and various design parameters on the relative stability and crosstalk delay of the coupled interconnects is investigated. It is shown that crosstalk effect makes the coupled interconnect system more stable than that in a single interconnect case. Moreover, increasing the wire length and edge roughness, the coupled interconnects becomes more stable due to the raise in crosstalk delay. Whereas, the increase of wire width, space and doping density, the crosstalk delay decreases, and the coupled interconnects is less stable. The time response for the step input verifies the analysis mentioned above. The results presented in this paper are useful for the design of reliable MLGNR interconnects with better propagation characteristics.